“Diseño de un plan estratégico de marketing para la empresa Hazwat Cía. Ltda., dedicada a la prestación del servicio de transporte, tratamiento y disposición final de desechos peligrosos ubicada en Otón vía Quito-Cayambe” - Collaguazo Chiguano, Mayra Janeth (2015)
Hazwat Cía. Ltda., Is dedicated to transport special and hazardous waste for treatment go hand in hand with the facilities of the Center for Environmental Remediation (CRA), which operate in an appropriate manner in the destruction of waste without harming the environment, which to implement the environmental license and the new furnace waste destruction is intended to increase the volume of production and sales and guarantee if the quality of service, the company is regarded as a pioneer in its sector in environmental management. By performing a thorough investigation of administrative staff and external factors of the company internal factors of the company, plant, machinery and which allowed to determine the profitability of the company will be favorable, that is how the company periodically assesses the environmental impact and awareness of care. Having described the current situation where important issues such as the mission, vision and policies which allowed developing a SWOT analysis, and was identified by establishing the Strategic Marketing Plan for the company advertising strategies will be proposed to be improving the picture and go increased customer base and projected it into the future by being more competitive. One of the strategies proposed is the creation of the marketing area as the proposed strategies to implement the institution to increase its production in waste incineration obtaining high monetary benefits and creating jobs. It is intended to implement the Strategic Marketing Plan growth and strengthening Hazwat Cía. Ltda. which is recognized in the environmental market.